Blood Pressure, Urine, and Blood Test Barriers During Antenatal Care in Bangladesh: An Analysis of MICS 6 - Rahayu, Yayu Puji; Noor, Irfan Nowroze; Barkinah, Tut (AMPLITUDO : Journal of Science and Technology Innovation, 2024)
Antenatal care is important during the pregnancy. During that, pregnant women will be tested for blood pressure, urine, and blood test as the essential information for mother and baby. This study purposed to examine the factors impact to inaccessibility of blood pressure, urine, and blood test. This study used the secondary data using “Multiple Indicators Clusters Survey” round 6 in 2019. Total sample of this study are 7,607 women who experienced antenatal care services. The data analysis was done for univariate, bivariate, and multivariate using binary logistic regression. The results in this study revealed that educational level and wealth index as the main predictors of inaccessible tests during antenatal care. Increasing level of education and wealth index will decrease the barriers to access testes. Government and stakeholders can focus on education and economics sectors to increase the accessibility to antenatal care especially for blood pressure, urine, and blood test services.